Evaluation of Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio in patients with subclinical hypothyroidism - Gürdal, Ahmet (Ther Adv Endocrinol Metab, 2017)
BACKGROUND: Prolongation of the peak-to-end interval of the T wave (Tp-e) has been reported as associated with ventricular arrhythmias. The aim of this study was to investigate the ventricular repolarization by using the Tp-e interval, Tp-e/QT ratio and Tp-e/ QTc ratio in patients with subclinical hypothyroidism (SH). METHODS: We studied 56 volunteers: These were 28 patients with SH (mean age 45 ± 11 years) and 28 healthy subjects (mean age 34 ± 8 years). All basic biochemical parameters were analyzed and electrocardiograms (ECGs) were recorded. RR and QT intervals, QTc, Tp-e intervals and the Tp-e/QT and Tp-e/QTc ratios were calculated. The categorical and numerical variables were compared using the chi-square test and independent t test, respectively. Correlations were analyzed using the Spearman and Pearson correlation tests. RESULTS: We found no difference between QT and QTc intervals between groups. In the subjects with SH, the Tp-e intervals (87 ± 5 ms, 66 ± 5 ms, p < 0.01), Tp-e/ QT ratio (0.23 ± 0.03, 0.18 ± 0.01, p < 0.01) and Tp-e/QTc ratio (0.21 ± 0.02, 0.16 ± 0.01, p < 0.01) were increased compared with healthy subjects. We also found positive correlations between levels of thyroid stimulating hormone (TSH) and Tp-e (r = 0.72, p < 0.01), Tp-e/ QT ratio (r = 0.67 p < 0.01), Tp-e/ QTc ratio (r = 0.68, p < 0.01). In the subjects with SH, Left Ventricular Myocardial Performance Index (LV-MPI) was increased compared with the healthy subjects (0.64 ± 0.08, 0.59 ± 0.09, p = 0.066) although it was not significant. CONCLUSIONS: Compared with healthy subjects, patients with SH demonstrated longer Tp-e intervals, and higher Tp-e/QT and Tp-e/QTc ratios. TSH levels were positively correlated with Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio.